Trend and disparities in authorship of healthcare-related publications on the ongoing Russia-Ukraine war - Habib Olatunji Alagbo; Saloni Mitra; Karen Madueke; Uchechi Blessing Azuwike; Samantha Dos Santos Rocha Ferreira; Alimat Temitope Ademuyiwa; Oluwaseun Adeleke; Chigozirim Ejinkeonye; David Izuchukwu Onyebuchi; Inioluwa Atowoju; Faith Inioluwa Odelola; Jyoti Kumari; et al. (BMC, 2023)
Abstract Background The Russia-Ukraine war has undeniably impacted global science and healthcare in Ukraine. Many Ukrainian researchers have had their projects disrupted by this war, either due to loss of life, displacement, or destruction of resources. Despite these challenges, these researchers have sought to make their voices heard. This scoping review highlights the trend of healthcare-related publications on the current Russia-Ukraine war and characterizes the contribution of Ukrainian authors to these publications. Method A comprehensive literature search was performed using two databases (Scopus and Pubmed) for publications related to the ongoing Russia-Ukraine war. We included articles only related to healthcare. We then extracted and analyzed bibliometric data. Result One hundred and eighty-three articles were identified, including 12 (6.6%) original articles, 26 (14.2%) cross-sectional studies, 19 (10.4%) letters to the editor, 10 (5.5%) commentaries, 5 (2.7%) perspectives, 35 (19.1%) editorials, 2 (1.1%) randomized controlled trials, 11(6.0%) correspondences, 13 (7.1%) opinions, 8 (4.4%) reviews and 42 (23.0%) are identified as others. 180 (98.4%) studies were in English, and 3 (1.7%) were in German. 54 (29.5%) papers on the war had at least one author affiliated with a Ukrainian institution, and 29 (15.9%) studies had authors with Ukrainian affiliation as first authors. Conclusion our study shows that there has been a significant number of publications on the Russia-Ukraine war and only a small portion of first authors, co-authors, and last authors of these publications are affiliated to an institution in Ukraine. Therefore, despite the relatively high number of publications, most publications do not arise from the perspective of Ukrainian authors.